The nexus between refugee settlements and environmental degradation in the Somali Region, Ethiopia - Mekuria, Wolde; Girma, R.; Seid, Abdulkarim; Ruckstuhl, Sandra (International Water Management Institute, 2025)
The rapid growth and prolonged presence of refugee settlements in ecologically fragile landscapes create complex humanitarian, environmental, and social challenges, yet evidence on their spatial impacts is limited. Policymakers and humanitarian actors require this understanding to inform sustainable planning of refugee settlements, mitigate ecological degradation, and promote peaceful coexistence. This study examines the link between refugee settlements and environmental degradation in Ethiopia’s Somali region, home to over 268,000 refugees in eight camps. Objectives were to: (i) map camps and assess spatial impacts on land use/cover, soil erosion, and land degradation neutrality; and (ii) identify influence zones and recommend interventions for sustainable planning. Using satellite imagery, rainfall, topographic, and soil data (1985–2024) with ArcGIS, buffer zones of 0–5 km, 5–10 km, and 10–15 km around camps were analyzed for land use change, erosion (RUSLE), and degradation neutrality (SDG indicators). Results show significant land cover loss and soil erosion, especially within 0–5 km zones, where forests, shrublands, and waterbodies declined by 90–100%, replaced by settlements and farms. Erosion shifted from low (0–7 t ha⁻¹) to severe (45–60 t ha⁻¹), notably in Sheder, Awbarre, and Bokolmayo camps. Degraded land expanded across all zones, reducing ecosystem recovery. The findings underscore the nexus between refugee settlements and environmental degradation, with significant implications for: (i) Ecosystem services and livelihood: Loss of vegetation and water resources undermines the livelihoods of both refugees and host communities; (ii) Social tensions: Competition over scarce resources may exacerbate conflict and reduce resilience; and (iii) Policy and planning: Current settlement practices might be unsustainable without integrated environmental consideration. We suggest that future refugee camps in Ethiopia’s Somali region and in other similar areas with fragile ecosystems should be established after assessing land degradation, erosion risk, water availability, and biodiversity within at least a 15 km buffer zone, among others. Camp design and management must integrate soil and water conservation, reforestation, sustainable land use, alternative energy, and ecosystem restoration to limit degradation and support long-term resilience for refugees and host communities.